Synthetic peptides modulate epithelial junctions - Yi, Sheng (Kansas State University, 2009)
Peptides based on the second transmembrane segment of the glycine receptor (M2GlyR) were made to provide a potential therapeutic treatment for cystic fibrosis (CF) and a latent absorption enhancer for drug delivery. For similarity of presentation, unique synthetic peptide sequences have been given alpha-numeric designations. Results are presented from studies focusing on four peptides. In the first study, the contributions of synthetic peptides p1171, p1172 and p1173 to net transepithelial ion transport were measured as a first step toward the goal of testing whether pore length or electrostatics of pore lining residues will affect anion transport. Peptide p1130 exhibits many attributes that make it an ideal synthetic peptide for CF treatment, but has low permselectivity for anions. Therefore, it is used as a platform for modification. Peptide p1171 is doubly substituted with diaminopropionic acid at positions T13 and T17. Peptide p1172 and p1173 are separately one and two helical turn(s) inserted into the p1130 backbone. Apical exposure of MDCK monolayers to these peptides caused a rapid increase in short circuit current (Isc), an indicator of net ion transport. The increase in Isc caused by p1172 or p1173 was accompanied by increase in transepithelial electrical conductance (gte). The electrophysiological results suggested that these modified peptides can assemble in the apical membrane of epithelial cells to form functional ion-conducting pores. Peptide NC-1059, which provides for ion transport across epithelial cells derived from many sources, was studied further to assess cellular changes that account for increased gte. NC-1059 increased Isc, gte and enhanced permeation of dextrans in a concentration dependent manner. Results from previous and current studies show that NC-1059 modulated the epithelial paracellular pathway by altering the distribution and abundance of junctional proteins. Immunoblotting and immunolabeling with confocal microscopy showed that NC-1059 induces reorganization of actin and causes a reduction in F-actin abundance in epithelial cells. The distributions were changed and cellular abundances were reduced of tight junction proteins occludin and ZO-1 and adherens junction proteins E-cadherin and β-catenin by NC-1059. These effects were largely reversed in 24 hr and fully recovered in 48 hr. Therefore, NC-1059 has the therapeutic potential to increase the efficiency of drug delivery across barrier membranes.
Keywords: Synthetic peptides; Occludin; ZO-1; Actin; Paracellular permeability; Transepithelial conductance; Biology, Cell (0379); Chemistry, Biochemistry (0487)